Early and late diagnosed dyslexia in secondary school: Performance on literacy skills and cognitive correlates - Bazen, Loes (Dyslexia, 2020)
Although a diagnosis of dyslexia is often made during elementary school, severe and persistent literacy difficulties of a considerable group of students are only noticed during secondary school. The question arises whether the literacy(‐related) deficits of these late identified students with dyslexia differ from those of early diagnosed students. To address this question, 10th Grade Dutch secondary school students with early (n = 35) and late (n = 19) identified dyslexia and their peers with average to good literacy abilities (n = 24) were compared on literacy skills and underlying cognitive skills. At the group level, both students with an early and late diagnosis performed more poorly than their typical peers, but they did not differ from each other on (pseudo‐)word reading, spelling and underlying cognitive correlates (phonemic awareness, rapid automatized naming and visual attention span). The early and late group contained comparable percentages of students performing poorly on most measures. There were, however, more students in the early group who showed deficits in phonemic awareness. Our results indicate that students with early and late diagnosed dyslexia are highly comparable. Suggestions for fitting interventions are discussed.